Crowdfunding: A new phenomenon of philantrophic method / Nurzahidah Jaafar … [et al.] - Jaafar, Nurzahidah; Syed Abdullah, Sharifah Fadylawaty; Daud, Mohd Zaid; Mohd Nasir, Mazni Natasha (2017)
Raising money for whatever purpose can be a daunting process. Great ideas without the financial clout that will turn them into profitable ventures inevitably fizzle out. Crowdfunding, a practice of funding a venture by raising money from a large number of people, has grown in popularity as of late and allowing entrepreneurially skilled individuals to request funding from the public or crowd, which in return will get the product. Yet, this philanthropic platform is still unfamiliar amongst Asian Community due to lack of understanding and technological development within this region. The primary objective of this article is to explain the application of the crowdfunding concept through selected established model for the benefit of society in order to be more aware of this platform. In conclusion, it is hope this article will give advantages for the betterment of socioeconomic and education in Malaysia.